De São Paulo À Olinda: Da Emersão À Fixação Da Filosofia No Brasil. - Nogueira, Alex Silva [UNIFESP] (2018)
The Purpose Of This Research Is To Analyze The Origin Of Philosophy In Brazil And Its Relation With The Men Who Would Receive The Title Of Intellectuals, Through The Philosophical Formation And Occupy Positions And Public Functions Before The Newly Formed Brazilian State. Our Hypothesis Begins With The Emergence Of The Brazilian Philosophy That Originated In The Faculties Of Law (From The Nineteenth Century) And Helped The Formation Of Statesmen And, In Turn, The State. The First Contact With Philosophical Knowledge Occurred Through The Training Of Law Graduates Who Appropriated The Tools Derived From Philosophical Knowledge And Such Historical Knowledge Was Fundamental To Effect Departmentalism And Hegemonic Control Of Political Power. However, The Foreign Internalization Of European Philosophy, By Its Molds And Clearly By Its Influences, Contributed To The Formation Of Knowledge And Thoughts That Would Enable The Creation Of Notable Brazilian Thinkers. Accordingly, The Emergence Of Philosophy In Brazil Occu